2003
DOI: 10.1128/jb.185.13.3962-3965.2003
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Monooxygenase Involved in the Biosynthetic Pathway of the Antitumor Drug Mithramycin

Abstract: A monooxygenase encoded by the mtmOIV gene from the mithramycin gene cluster of Streptomyces argillaceus was purified 21-fold by a three-step purification procedure. This monooxygenase catalyzes the oxidative cleavage of the fourth ring of premithramycin B. The enzyme was dependent on NADPH and flavin adenine dinucleotide for activity with optimal pH at 9.5, and the K m values for NADPH and premithramycin B were 269.22 and 23.35 M, respectively. The reaction catalyzed by MtmOIV yields two possible isomers of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 9 publications
1
33
0
Order By: Relevance
“…In 1959, more than 10 years after the first indications of the existence of an enzymatic version of the BaeyerÀVilliger oxidation during the bioconversion of steroids, Bradshaw et al reported the microbial degradation of (þ)-camphor (26) with Pseudomonas putida isolated from sewage sludge. 104 Although no biochemical studies were presented in this initial paper, the isolation of two lactone metabolites indicated the existence of BVMO activity in P. putida.…”
Section: Baeyeràvilliger Monooxygenases In the Metabolism Of Terpenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1959, more than 10 years after the first indications of the existence of an enzymatic version of the BaeyerÀVilliger oxidation during the bioconversion of steroids, Bradshaw et al reported the microbial degradation of (þ)-camphor (26) with Pseudomonas putida isolated from sewage sludge. 104 Although no biochemical studies were presented in this initial paper, the isolation of two lactone metabolites indicated the existence of BVMO activity in P. putida.…”
Section: Baeyeràvilliger Monooxygenases In the Metabolism Of Terpenoidsmentioning
confidence: 99%
“…25 In the biosynthetic pathway of an anticancer antibiotic called mithramycin by the soil bacterium Streptomyces argillaceus ATCC 12956, a BVMO named MtmOIV was found to be responsible for the conversion of a biologically inactive precursor, premithramycin B (3) to the corresponding lactone 4 that is further converted to mithramycin DK presumably by lactone opening and decarboxylation, and finally into the active drug mithramycin (5). 20,26 MtmOIV is believed to catalyze more than the fourth ring modification of premithramycin but also the various followup reaction steps. 20 MtmOIV is regarded as the first example of a naturally occurring BVMO with its cognate substrate ( Figure 4).…”
Section: Function and Significancementioning
confidence: 99%
“…Its aglycon including the 3-side chain is biosynthesized from 10 acyl-CoA units by a type II polyketide synthase, and all five deoxyhexose moieties are successively attached to the tetracyclic intermediate premithramycinone, resulting in the fully glycosylated intermediate premithramycin B via premithramycin A 3 , 1-7 before an oxidative cleavage reaction, catalyzed by Baeyer-Villigerase MtmOIV, 3,5,7 followed by the reduction of a side chain keto group by MtmW, finishes the biosynthesis (Scheme 1). The glycosylation steps remain partly obscure, although the sequence could be established unambiguously: initially, the trisaccharide chain is formed through successive glycosylation steps, before the disaccharide chain is attached, also in a stepwise sequential order.…”
mentioning
confidence: 99%
“…All of these biosynthetic intermediates have been isolated from mutants blocked at different steps in biosynthesis and share a common feature, which is the pres-ence of a tetracyclic aglycon. The final tricyclic structure of MTM is obtained after the oxidative cleavage of the fourth ring of premithramycin B, in a reaction catalyzed by a monooxygenase and followed by the ketoreduction of the 4Ј-position of the generated aliphatic chain (9,12). This renders the fully biologically active compound.…”
mentioning
confidence: 99%
“…It has been clinically used for the treatment of testicular carcinoma, Paget's bone disease, and other bone growth disorders and is also used for control of hypercalcemia in patients with malignant disease (4). The biosynthetic pathway for MTM biosynthesis has been extensively studied by biochemical and genetic means (2,(5)(6)(7)(8)(9)(10)(11)(12). Although MTM is a tricyclic aromatic polyketide with a side chain, its biosynthesis proceeds through tetracyclic tetracycline-like intermediates (6).…”
mentioning
confidence: 99%